Balancing Energy Consumption and Connectivity through Energy-Efficient Protocols for Sustainable Networking in Smart Cities - Chaudhry, Uroosa Bilal; Ahmed, Tauqir; Wajid, Amna (The Nucleus, 2024)
This paper focuses on the challenges and opportunities of achieving sustainability in smart cities. It depends on maintaining the balance between energy efficiency and connectivity through energy-efficient protocols. The study surveys systems with energy-efficient protocols, emphasizing their strengths and limitations in maintaining sustainability in smart cities. The need for energy-efficient protocols in smart city settings is that these protocols dynamically adjust operations to optimize energy consumption within sensor nodes in communication networks while considering parameters: like heterogeneity, traffic patterns, and environmental factors. Evaluation against key performance metrics such as energy consumption, data delivery ratio, network lifetime, and throughput identify promising technologies to achieve an optimal balance between connectivity and energy efficiency in smart cities. It concludes by proposing future research directions and considerations to make the development of sustainable networking solutions rapidly tailored to the evolving landscape of smart cities. This paper aims to present a comprehensive overview of the pivotal role played by energy-efficient protocols in fostering sustainable networking architectures.